PERANAN SEKTOR PERTANIAN TERHADAP PEREKONOMIAN KABUPATEN ROKAN HILIR: ANALISIS STRUKTUR INPUT-OUTPUT - Siti Khoyanah; Djaimi Bakce; Jum’atri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The agricultural sector is very important on the economy Kabupaten Rokan Hilir as industrial raw material providers, employers, providers of food and source of income. This study aims to analyze the role of agriculture sector to the economy of Kabupaten Rokan Hilir through input-output structure of the review. The data used is data input-output Kabupaten Rokan Hilir 2011 with 19 x 19 sector classification which derived from the Bappedaof Kabupaten Rokan Hilir. The analytical method used is descriptive analysis method.The analysis showed that: 1) the agricultural sector give the high contribution to the economy of Kabupaten Rokan Hilir. Agricultural sector which give the high contribution are the plantation sector and fisheries sector.2) The output forming components of agricultural sector which is seen from the output is driven by investment, followed of exports and intermediate output. 3) In terms of the role input of agricultural sector is driven by the producersurplus, wage-salaries and intermediate input.Based on the results, to encourage economic growth of agricultural sector, it is needed increase the investment directly or indirectly. Effort to improve the investment indirectly through the accumulation of capital from producer surplus.   Keywords: agricultural, input-output table, investment and producersurplus.